Meaning in Malay- English Dictionaries: An Application of Frame Semantics and the Framenet - Intan Safinaz Zainudin; Nor Hashimah Jalaluddin; Imran Ho Abdullah (Kajian Malaysia, 2014)
A literature review of bilingual dictionary research in Malaysia shows that most research has focused on the problems of equivalents recorded in bilingual dictionaries. What is lacking is proper linguistic analysis of the discrimination of meaning for the source language entry and the findings of the target language equivalents. This paper attempts to fill this research gap by investigating the problems that arise in the discrimination of meanings of two Malay-English dictionaries, and the English equivalents. The analysis adopts the methods of frame semantics in describing the Malay verb memberi, assessing the different senses of meaning through the frames that are available. The theoretical framework of Frame Semantics has successfully helped the writer to reorganise the meaning of the Malay transitive verb memberi (translation in English "give") from the different frames evoked by the entry. Meanwhile, the information of the lexical units (LU) provided by the frames, for example the LUs from the frame of GIVING in the FrameNet database have contributed to a list of English equivalents that can be used in the Malay-English dictionary entry. This framebased analysis relies on the 5 million words Dewan Bahasa dan PustakaUniversiti Kebangsaan Malaysia (DBP-UKM) Malay corpus while all the English equivalents are sourced from FrameNet and English dictionaries.